2014
DOI: 10.1139/cgj-2013-0241
|View full text |Cite
|
Sign up to set email alerts
|

Fluid loss as a quick method to evaluate hydraulic conductivity of geosynthetic clay liners under acidic conditions

Abstract: This study investigates the performance of bentonite components of geosynthetic clay liners (GCLs) when exposed to aggressive leachates using the fluid loss test and provides a possible quick method for estimating the effect of acidic conditions on hydraulic conductivity. Fluid loss generally increases with increasing acid concentrations. Hydraulic conductivity values back-calculated from the fluid loss tests (kFL) are compared with the values measured using a flexible-wall permeameter (kTri). Generally, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…All GCL coupons yielded similar fluid loss values to the virgin bentonite regardless of in-field history, and are similar to those reported elsewhere (Liu et al, 2013(Liu et al, , 2014. None of the samples tested had fluid loss greater than the required maximum value of 15 mL.…”
Section: Fluid Loss Propertiessupporting
confidence: 82%
“…All GCL coupons yielded similar fluid loss values to the virgin bentonite regardless of in-field history, and are similar to those reported elsewhere (Liu et al, 2013(Liu et al, , 2014. None of the samples tested had fluid loss greater than the required maximum value of 15 mL.…”
Section: Fluid Loss Propertiessupporting
confidence: 82%
“…Numerous experimental studies have been conducted to investigate the hydraulic and contaminant transport properties of conventional GCLs consisting of loose, granular or powdered Na bentonite held between two geotextiles (e.g., Boardman and Daniel, 1996;Lin and Benson, 2000;Lake and Rowe, 2000;Shackelford et al, 2000;Jo et al, 2001;Malusis and Shackelford, 2002a,b;Shackelford and Lee, 2003;Benson et al, 2010;Lange et al, 2010;Shackelford et al, 2010;Kang and Shackelford, 2011;Rowe and Hosney, 2013;Bouazza and Gates, 2014;Hosney and Rowe, 2014;Liu et al, 2014Liu et al, , 2015Makusa et al, 2014), such as the GCL shown in Fig. 1a.…”
Section: Introductionmentioning
confidence: 99%
“…To make sure the fluid loss additive has an excellent ability of absorption, the monomer with strong absorption groups, such as amino-group, are introduced [12,13]. To make sure the additive has an excellent ability of salt tolerance, the monomers with stable group which is not sensitive to the cation, such as -SO 3 − , are introduced [14][15][16]. To make the fluid loss additive have an excellent ability of temperature resistance, the monomers with inflexibility groups such as big side group are introduced.…”
Section: Introductionmentioning
confidence: 99%